Transformasi Dakwah dan Konseling di Era Digital: Pemanfaatan Teknologi Komunikasi - Ellyzia Zahra Alidia; Naifa Rahma Nurzalia; Robiah Nur Adawiyah; Dwi Agus Santoso (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2025)
The development of digital technology has brought about major changes in the spread of da'wah and the implementation of Islamic counseling. Da'wah that used to focus on face-to-face is now transformed through social media and digital platforms, so that religious messages can reach a wider audience without time and space limitations. Digital media presents opportunities for da'i to convey da'wah with varied and interesting content, especially for the younger generation. However, challenges remain, such as the lack of direct emotional interaction and the difficulty of monitoring potentially deviant content. Meanwhile, Islamic counseling in the digital era is developing through online services, either through websites, telephones, chats, and video conferences. These services facilitate access to counselling, reduce distance barriers and social stigma, and provide flexible counseling alternatives. However, online counseling also has weaknesses, such as limitations in reading body language, network technical constraints, and counselors' skills that are not optimal in utilizing technology. Thus, Islamic da'wah and counseling in the digital era require the readiness of human resources, mastery of technology, and the application of good ethics in order to run effectively, professionally, and provide wide benefits to society.